Studi Kelayakan Bisnis pada UMKM Rempeyek 4 Sekawan : Strategi Analisis SWOT - Erlangga Aditya Pratama; Sinta Sukmawati; Putri Mahabbatun Aliyah; Maisya Hayina Zahra; Perwito Perwito (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
In the era of globalization, strong economic development is a priority for every country, with a significant focus on the role of Micro, Small, and Medium Enterprises (MSMEs). Using a qualitative descriptive approach of the field research method through interviews by utilizing field research to evaluate Rempeyek's business feasibility study. This research highlights the fundamental contribution of MSMEs to the national economy, especially in addressing issues such as poverty, unemployment, and income distribution. The study emphasizes the importance of understanding market opportunities and capitalizing on them through innovative product offerings that appeal to consumers. One of these promising businesses is the culinary business